2016
DOI: 10.1123/jmld.2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vision and Movement Automization on the Focus of Attention Effect

Abstract: According to the constrained action hypothesis, an external focus of attention is beneficial for motor learning due to improvements in movement automization. In contrast, an internal focus of attention interferes with automaticity and decreases the effects of motor learning. This study was designed to test the automaticity assumption of the focus of attention effect within a highly skilled population. We examined the effects of attentional focus on kinematics in rope jumping and visual control. Participants pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…There is a clear gap for our understanding of attentional focus on motor learning for periods longer than three sessions, yet shorter than four weeks. Except for the five sessions used by Porter et al (2016), and the nine weeks of training used by Makaruk et al (2012), we are aware of no evidence that examines training with an external focus for more than three sessions.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…There is a clear gap for our understanding of attentional focus on motor learning for periods longer than three sessions, yet shorter than four weeks. Except for the five sessions used by Porter et al (2016), and the nine weeks of training used by Makaruk et al (2012), we are aware of no evidence that examines training with an external focus for more than three sessions.…”
Section: Introductionmentioning
confidence: 88%
“…While these studies are imperative to our understanding of attentional focus, they are limited by the short duration of practice time which minimizes our understanding of the within and between day motor learning trajectories. The majority of studies exploring attentional focus have participants practice 20-100 trials over the course of one session (Chiviacowsky, Wulf, & Wally, 2010;Wulf et al, 1998;Wulf, Weigelt, Poulter, & McNevin, 2003), three sessions (Laufer, Rotem-Lehrer, Ronen, Khayutin, & Rozenberg, 2007), or five sessions (Porter, Makaruk, & Starzak, 2016), and assess learning via a retention test 24 hours later. However, there is a substantial jump in the attentional focus literature from the single or few session acquisition periods used, to large scale training studies of four weeks (Landers et al, 2015) and nine weeks (Makaruk, Porter, Czaplicki, Sadowski, & Sacewicz, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Just prior to each trial, participants were given the appropriate attentional focus instruction for the condition. Instructions for the baseline trial were to “simply perform as many jumps as you can during the 15 s bout.” Instructions given prior to the two upper-body focus conditions were similar to those used by Porter et al (2016) . The instruction for the upper-body external focus condition (UPEX) was to “focus on making small, fast ovals with the tips of your handles.” Instruction for the upper-body internal focus condition (UPIN) was to “focus on making small, fast ovals with your wrists.” For novices, the UPIN and UPEX instructions were simplified to ensure proper understanding.…”
Section: Methodsmentioning
confidence: 99%
“…The external focus benefit has been documented for a variety of discrete skills such as dart throwing, golf putting, free throw shooting, and standing long jump (e.g., Zachry et al, 2005 ; Poolton et al, 2006 ; Marchant et al, 2007 ; Becker et al, 2018 ). A smaller body of research has also shown benefits of an external focus of attention for the performance of continuous tasks such as swimming, jump roping, and balance ( Freudenheim et al, 2010 ; Porter et al, 2016 ; Rhea et al, in press ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study by Ford, Hodges, Huys, and Williams (2009) suggested that in skilled and novice football players, focusing on the ball trajectory (external) during football-specific exercises was more beneficial for motor performance (movement kinematics) compared with focusing on the body. Several other studies have shown gains in balance and greater whole-body coordination patterns (Flores, Schild, ANNA BODASIŃSKA, JANUSZ ZIELIŃSKI, HUBERT MAKARUK - Chiviacowsky, 2015;Porter, Makaruk, & Starzak, 2016) when an external focus of attention is adopted rather than an internal focus.…”
Section: Introductionmentioning
confidence: 93%